Water's behaviour on Ca-rich tricalcium silicate surfaces for various degrees of hydration: A molecular dynamics investigation - Claverie, Jérôme [UNESP]; Bernard, Fabrice; Cordeiro, João Manuel Marques [UNESP]; Kamali-Bernard, Siham (Elsevier, 2019)
Tricalcium silicate (C 3 S) hydration is a highly relevant topic toward a better understanding of ordinary Portland cement. Molecular Dynamics (MD) simulations can provide relevant information about water behaviour at interface with mineral surfaces. For the first time, the influence of C 3 S protonation on water structure and dynamics is assessed by simulating the Ca-rich (040) surface in contact with water. The recently extended INTERFACE force field for C 3 S, including parameters for hydroxyl and silanol groups, was used to perform classical MD calculations. The water layered structure arising from strong hydrogen bonding with the mineral surface decays with increasing hydration of the first atomic layer. We found that the presence of hydroxyl and silanol groups, as well as desorption of calcium cations strongly influence the structural and dynamical properties of water.
Keywords: Hydration; Hydrogen bonding; Molecular dynamics (MD) simulations; Tricalcium silicateC 3 S